Skin temperature variations as a tracer of microvessel tone. (August 2015) - Frick, Peter; Mizeva, Irina; Podtaev, Sergey
Abstract : Graphical abstract: Abstract : Highlights: Detailed comparison of wavelet correlation and Fourier coherency is presented. We measured simultaneously LDF and skin temperature in rest conditions. Pulsations of blood flow and skin temperature are correlated for 0.01–0.1 Hz. Phase shift between LDF and ST pulsations at low frequencies is found. Microvascular oscillations are reconstructed from skin temperature records. Abstract: The problem of frequency-by-frequency cross-correlation detection is studied using two characteristics of blood microcirculation: blood flow and skin temperature. Skin blood flow variations are measured by Laser Doppler Flowmetry (LDF) and Skin Temperature (ST) – by a high-resolution (0.001 K) temperature recorder. The wavelet cross-correlation (WCC) is compared with Fourier coherence and demonstrates certain advantages for the frequency-by-frequency analysis of biomedical nonstationary signals. The WCC analysis of the LDF and ST signals performed for 17 healthy subjects reveales a high correlation in the low-frequency range 0.01 < ν < 0.1 Hz. The WCC function provides the phase difference between the oscillations of LDF and ST signals. This phase shift is used to estimate the effective depth of temperature wave generation. Taking into account the decay rate of temperature oscillations at each frequency and the LDF-ST phase shift, we perform an inverse wavelet transform for the frequency band that corresponds to active mechanisms of vascular tone regulation. This technique allows us to recover the filtered ST signal from the LDF signal and vice-versa. It is shown that the ST pulsations mirror the functional state of the microcirculation system and the ST monitoring can be used for microvessels tone control within the frequency ranges corresponding to endothelial, neurogenic and myogenic activities.